HOUSING AS AN EXPRESSION OF SELF-IDENTITY IN CONTEMPORARY ALGERIA: THE WORK OF EL-MINIAWY BROTHERS - Bellal, Tahar (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2010)
This paper tries to shed light on post-traditional environment in Algeria in a post global civilisation era. Some chosen projects implemented in some parts of the country are dealt with in relation to the expression of self identity through housing architecture. The focus of the work is on methods, achievements and implications of the projects. As from the seventies of the last century Algeria witnessed dramatic changes in its physical environment. The cities became the focus of international construction activities and many internationally renowned architects competed for large scale projects (Oscar Niemeyer, Ricardo Boffil, Kenzo Tang, etc). The projects chosen in this paper all deal with housing and include a housing scheme in Maadher near Msila, the second example in El Oued, the third is a housing project in Ouled Djellal. All of these projects by El Miniawy brothers disciples of the late Hassan Fathy, address critical aspects of the built environment. Yet one can consider these projects as representative of architectural thinking and activity in the country. This working paper reveals general aspects to gain comprehensive understanding, rather than statistical knowledge of Algerian built environment.